2012
DOI: 10.1007/s10499-012-9497-5
|View full text |Cite
|
Sign up to set email alerts
|

Modulating gut microbiota and digestive enzyme activities of Artemia urmiana by administration of different levels of Bacillus subtilis and Bacillus licheniformis

Abstract: The aim of this study was to evaluate the effects of Bacillus subtilis and Bacillus licheniformis on growth, gut microbiota, and digestive enzyme activities of Artemia urmiana. Three diets containing 10 2 (T 1 ), 10 4 (T 2 ), 10 6 (T 3 ) CFU of probiotics/g feed, and a control diet (C) without probiotic were used through a completely randomized design (treatments with triplicates). Twelve plastic tanks with the capacity of 60-l and density of 20 nauplii/ml were used and the trial continued for 15 days. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…from clinical and environmental samples, some studies may classify total bacterial counts on TCBS as Vibrio spp. [48,49]. However, our results revealed that at least 19.0% of the bacteria isolated on TCBS agar submitted to MALDI-TOF MS identification did not belong to the genus Vibrio, being Photobacterium and Aeromonas the most frequently identified genera.…”
Section: Discussionmentioning
confidence: 55%
“…from clinical and environmental samples, some studies may classify total bacterial counts on TCBS as Vibrio spp. [48,49]. However, our results revealed that at least 19.0% of the bacteria isolated on TCBS agar submitted to MALDI-TOF MS identification did not belong to the genus Vibrio, being Photobacterium and Aeromonas the most frequently identified genera.…”
Section: Discussionmentioning
confidence: 55%
“…Probiotic Bacillus species are beneficial for modulating the intestinal microflora and micro-ecological balance ( Motlagh et al, 2012 ; Wang et al, 2017 ; Luo et al, 2020 ). In the present study, the increased intestinal microbiota barrier by the L-alanine-induced spores was further confirmed in the SD rats ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…LAB is recognized as a part of the microflora of rotifers (Gatesoupe, 1994), but its specific role is not yet fully understood. Applied to zooplankton cultures, B. subtilis acts as a growth promoter (Hirata et al, 1998;Murillo & Villamil, 2011;Zink et al, 2013); as a digestive enzyme promoter (Motlagh, Farhangi, Rafiee, & Noori, 2012); and as a pathogen inhibitor (Giarma et al, 2017;Murillo & Villamil, 2011).…”
Section: Discussionmentioning
confidence: 99%